Analisis Peran dan Struktur Pengorganisasian di IPWL bukit Doa Rumahku Rehabilitasi - Arifah Rkt, Azkyatul; Latipah Siahaan, Nur; Situmorang, Irsyad Baihaqi; Hasibuan, Seri Rosidah; Anggraini Siregar, Widya; Suraya, Rani (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2025)
Rehabilitation is an activity that is intended to help everyone who is classified as a drug abuser or addict by providing them with treatment, both medically and socially. The aim of this research is to realize the role and organizational structure so that it has an impact on the community, especially residents at IPWL Bukit Doa Rumahku Rehabilitation. This research method is a type of qualitative research with an empirical approach. The empirical approach is an approach that researches and collects primary data obtained directly from the research object through interviews with respondents and sources related to the research. The results of research based on knowledge, programs implemented, the impact of programs implemented, and existing facilities in rehabilitation organizations, show a positive impact on both the community and residents.